O uso da fotografia como instrumento no processo de orientação vocacional para adolescentes - Paternostro, Raquel C. C (2006)
This dissertation intends to reflect upon and illustrate the importance of the use of photography as a procedure of intervention in the process of vocational orientation, by means of theoretical concepts and fragments of a clinical case. The use of this resource in the process of vocational orientation enables the young to experience transitionality, allowing them to express creative aspects. This refers to the moment when the adolescent has to choose a profession, which causes him/her deep anguish and is many times dealt with denial. I want to point out the contribution of the experience of photography as an enabling instrument in the process, so that the choice results from an internal elaboration of the adolescent. The theoretical approach includes an historical overview of vocational orientation and of the concept of adolescence. I will emphasize Bohoslavsky s contributions as I agree with this author on the fact that professional and personal identity characterizes the individual, including different aspects of his/her development. I will also address the theory of human maturation of Winnicott, pointing out the concepts of potential space, transitional objects and phenomena; furthermore, I intend to include photography as a facilitative instrument to understand some aspects of the self. I will give a brief presentation of the work of some photographers who made use of the experience of photography in order to express their creativity inserted in culture, trying to base the use of photography on my clinical experience. The choice of this object of culture also reflects my personal experience as a photographer, which allowed me to be in touch with many aspects of myself until then unknown.